Design of super-twisting algorithm control and observer for three-phase inverter in standalone operation - Dinh Hieu Phan; Minh Tuan Dao; Van Truong Nguyen; Huy Anh Bui; Ngoc Duy Le; Thanh Lam Bui (Institute of Advanced Engineering and Science, 2022)
This paper develops a new control algorithm of a distributed generation system in the standalone operation. Behaviour of three-phase voltage source inverter is investigated and the guidelines for tuning the control parameters are presented. Based on Super-Twisting algorithm, the proposed controller guarantees the load voltage performance under different types of loads. The proposed controller is established for an inner-loop current controller and an outer-loop voltage controller in a dual control scheme. The proposed scheme is very simple, thus tuning control parameters is easy and the computational burden of the controllers is low. In order to validate the load current of the proposed system feasibility, a reduced-order observer is adopted. The simulation results indicate a more reliable and efficient performance compared to the standard sliding control and the adaptive control.